The Exclusion Of Application Of Foreign Law Provisions For Violating Islamic Sharia Law In Terms Of Article (27) Of The UAE Civil Transactions Law Amended By Federal Decree-Law No. (30) of 2020 - Mohamed, Nashwa; Rahma, Munira (Journal of Legal Sciences, 2023)
This study is about the subject of exclusion of the application of foreign law as it violates the Islamic Sharia law in terms of Article (27) of the UAE Civil Transactions Law as amended in 2020, which before that date included all disputes involving a foreigner. According to the amendment referred to, the application of Islamic Sharia law shall be limited to civil transactions with the exclusion of personal status affairs.The study concluded with many results, the most important of which is that the current text of Article (27) of the Civil Transactions Law as amended in 2020 is unable to explain what the judge may do in cases where the foreign law jurisdiction is referred to in one of the excluded texts, namely those related to personal status affairs contained in Articles 12 to 17 of the aforementioned law.The study came out with several recommendations, including that the UAE legislator is urged to reconsider the text of Article (27), which excludes personal status affairs, by including in its scope all texts previous to it, deleting the reference to Islamic law, and deeming the public order as sufficient; based on the fact that the Islamic Sharia law is part of the public order in the UAE.